Environmental and spatial drivers of diatom assemblages in the water column and surface sediment of tropical reservoirs - Bartozek, Elaine C. R. [UNESP]; Silva-Lehmkuhl, Angela M. da [UNESP]; Gregory-Eaves, Irene; Bicudo, Denise C. (Springer, 2019)
The relative contribution of environmental and spatial drivers of community structure has been the focus of many ecological studies. In the context of metacommunity theory, diatoms have been associated mainly with local environmental factors, but in some cases spatial factors have also been identified as important drivers. This study aimed to determine the relative importance of environmental and spatial drivers as predictors of surface sediment and water column diatom assemblages in tropical reservoirs. Sampling was carried out in 33 reservoirs in southeast Brazil, which range in trophic state from oligotrophic to hypereutrophic, and span five hydrological basins. We performed a partial RDA between the predictor matrices (environmental and spatial predictors) and the response matrix (either surface sediment or water column diatom assemblages) to identify the main environmental drivers, and used variation partitioning to assess the relative contribution of environmental and spatial predictors of diatom assemblages. In general, diatom assemblages were structured by a combination of environmental and spatial drivers. Comparisons of results between surface sediment and water column ordinations demonstrated that the assemblages were structured by similar environmental variables (productivity-related variables such as total phosphorus, water transparency and pH) and by a similar set of diatom species, mainly centric diatoms like Aulacoseira granulata var. granulata, A. tenella, Discostella stelligera and Spicaticribra kingstonii. Overall, surface sediment diatoms were more strongly associated with environmental factors than were water-column assemblages, probably because they integrate information in space and time, confirming that surface sediment assemblages are robust indicators of environmental conditions.
Keywords: Algae; Environmental predictors; Environmental gradient; Metacommunity; Spatial predictors